Corrigendum to "performance of bricks made using fly ash and bottom ash" (Constr. Build. Mater. (2015) 96 (576-580) 10.1016/j.conbuildmat.2015.08.068) - Naganathan S.; Omer Mohamed A.Y.; Jamali S.; Mustapha K.N. (Elsevier Ltd, 2023)
[No abstract available]